O trabalho e a educação carcerária no estado do Pará - ARAÚJO, Maria Auxiliadora Maués de Lima (Universidade Federal do Pará, 2020)
The article aims to strengthen the dialogues about the prison education, profiling the way how they effect the work as educational principle and the education, from a social perspective, on the prisons of the state of Pará. That has been sought by observing the fundamentals of prison education and its substantiation mechanisms. The proposal was based on a qualitative bibliographical research. The discussions were treated taking in account problems reported by evidences that aim to clarify a panorama about: who are the imprisoned youths on the state of Pará? What are the policies that guarantee education to the imprisoned in Brazil? What kind of educational works are offered and what are their contributions to the resocialization of the imprisoned? It is understood that the prison education lacks a more critical, reflexive eye on the hiatus between the official discourse and its practice on the prison space. That they are necessary attempts to enlarge and sharply improve the life of the prisoners. Actions that befall both on structural and attitudinal issues and, mainly, on the effetivation of educational policies that are fully capable of propositively contributing on the lives of that population. Clarifying the propositions for that educational field allows the constitutional guarantee of education as a right for all people, and allows imprisoned people the chance of, through labor and education, sighting contributive elements for their resocialization.